Metáforas e iconos para transmitir información - Aladro Vico, Eva (CIC. Cuadernos de Información y Comunicación, 2007)
The article explores the links between icons and digital information, in their coexistence, their cooperation and their complementarities in knowledge acquisition process. In cognitive theories as well as in today’ s neurobiology and in metaphor analysis there is a unanimous opinion about the importance of icons in organising and implicating the access to information.